Boundary controllability of impulsive nonlinear fractional delay integro-differential system. Issue 1 (31st December 2016) - Ahmed, Hamdy M.
Abstract: By using the strongly continuous semigroup theory and the Banach contraction principle, we study the boundary controllability of time varying delay impulsive nonlinear fractional integrodifferential system in Banach spaces. An example is provided to illustrate the theory.